Influence of Chemical Admixtures and Environmental Conditions on Initial Hydration of Concrete - Ribeiro, A. C. (2013)
There has been an increasing number of problems in concrete pavements, such as cracks and delamination, in which surface hardeners have been used, especially in car parks, industrial areas, warehouses etc. Factors that can potentiate the occurrence of these problems are the increasing use of more effective water reducers in concrete and also the use of binders with higher fineness and higher tricalcium silicate content than the former ones. Concrete and surface hardeners are both cementitious materials, which however are applied at different instants. Distinct stages of hydration may lead to lack of homogeneity and, eventually, to cracking and delamination. This study evaluates early hydration and bleeding behaviour of concrete, which are relevant factors for finishing with surface hardeners. The influence of chemical admixtures and environmental conditions were tested by penetration resistance and bleed water, which highlights the shortening of the period in which surface hardener application is possible.